CAR-T Cell Therapy in Hematological Malignancies: Current Opportunities and Challenges - Zhang, Xiaomin; Zhu, Lingling; Zhang, Hui; Chen, Shanshan; Xiao, Yang (Frontiers in Immunology, 2022)
Chimeric antigen receptor T (CAR-T) cell therapy represents a major breakthrough in cancer treatment, and it has achieved unprecedented success in hematological malignancies, especially in relapsed/refractory (R/R) B cell malignancies. At present, CD19 and BCMA are the most common targets in CAR-T cell therapy, and numerous novel therapeutic targets are being explored. However, the adverse events related to CAR-T cell therapy might be serious or even life-threatening, such as cytokine release syndrome (CRS), CAR-T-cell-related encephalopathy syndrome (CRES), infections, cytopenia, and CRS-related coagulopathy. In addition, due to antigen escape, the limited CAR-T cell persistence, and immunosuppressive tumor microenvironment, a considerable proportion of patients relapse after CAR-T cell therapy. Thus, in this review, we focus on the progress and challenges of CAR-T cell therapy in hematological malignancies, such as attractive therapeutic targets, CAR-T related toxicities, and resistance to CAR-T cell therapy, and provide some practical recommendations.